PENGARUH FAKTOR EKSTERNAL DAN NPL TERHADAP RETURN SAHAM PADA BANK KONVENSIONAL BADAN USAHA MILIK NEGARA - Muhammad Mirza Maulana (2022)
This research is using quantitative study aimed to see whether there are influence of inflation, interest rate, exchange rate, and NPL of stock return. This study uses the state-owned business entities. Testing the hypothesis in this study was used Multiple Linear Regression Analisys using SPSS analysis tool with a significant level of 0.05 %. The results of these tests indicate that (1)there is negative significant effect influence of inflation on the stock return, (2)there is no significant influence of interest rate on the stock return, (3)there is negative significant effect influence of exchange rate on the stock return and (4)there is no significant influence of NPL on the stock return.